MANFAAT WISATA ALAM DANAU WISATA SEJARAH SEBADDANG KECAMATAN SEBAWI KABUPATEN SAMBAS - Robihah, Uray; Roslinda, Emi; Widiastuti, Tri (Universitas Tanjungpura, 2014)
Danau Wisata Sejarah Sebaddang (DWSS) is one of the tourist attractions located in Sambas district, but most of the environmental services offered do not yet have a market value. Hence the need for an approach to determine the economic value of the benefits obtained in order to estimate the magnitude of demand and consumer surplus. The purpose of this study was to determine the benefits of recreation and makes predictions collecting admission price fixing. To achieve the purpose of the study used the Travel Cost Method. The object of research was the visitors who come to the DWSS. Recreation demand equation Y = 52,906 - 0,001X. At the ticket price Rp.6000,- /person has Rp.4.081,- consumer surplus value, visits to the value of the average willingness to pay Rp.10.081, - /person and the value of the economic benefits of Rp.72.772.392,- /year. This means that if the manager wants to improve tourist facilities it should at least be set ticket prices Rp.10.081,- /person. Key words : Sebaddang lake, benefit, natural recreation